Training of Gamified Online Learning for Teachers Through Quizizz - Aisyiah Al Adawiyah (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
In this pandemic, the class activity must be held online. Therefore, teachers should have learning media for teaching so students still can understand the material. ICT-based media exist to facilitate distance learning, but teachers must balance first their teaching method by implementing it. As one of the biggest applications used, Quizizz is easy to use in teaching and testing students synchronously. We organized the Quizizz training for Indonesian teachers on August 21 – 22, 2021 via Zoom to help teachers in know well Quizizz. We also gave further assistance across the WhatsApp Group to discuss the problem which they met during the Quizizz implementation. The result is they comprehend properly the Quizizz implementation based on two assignments in making quiz and lesson slides. They took advantage of the section to well facilitate online learning so their students can achieve the learning outcomes as well as in the offline class.